Implementasi Kurikulum Merdeka Dalam Pembelajaran IPAS Berbasis Proyek: - Dhira Andari Handewi Pramesti; Ahmad Ipmawan Kharisma; Rizka Novi Irmaningrum (Bidayatuna, 2023)
The implementation of Freedom of Learning in project-based IPAS and science learning has problems related to the implementation of the Curriculum. The implementation of project-based learning aims to: Understand the implementation of the Merdeka Curriculum in class IV project-based IPAS and science subjects at SDN. The research method uses observation, interviews, questionnaires and documentation. The data analysis techniques used by researchers are data reduction, data presentation and conclusions. Researchers used data validity testing with source triangulation techniques. This technique explains that the credibility test is to check data so that results such as interviews, questionnaires and documentation are obtained. The following results of this research confirm that: 1) First, at SDN, the implementation of Independent Learning Curriculum has begun to be implemented using project-based IPAS and science subjects. 2) Second, there are obstacles experienced by teachers resulting in the implementation of the Merdeka Curriculum, namely teachers have difficulty analyzing Learning Achievements, formulating several Learning Objectives and developing a Flow of Learning Objectives and Teaching Modules, lack of time allocation in project-based learning activities 3) Things that teachers do to solve the problem of implementing the Merdeka Curriculum, such as teachers carrying out regular training with the Kelompok Kerja Guru (KKG) and directing and mentoring with the head school.